2012
DOI: 10.1128/jvi.02225-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Human Adenovirus Type 55, a Re-Emergent Acute Respiratory Disease Pathogen in China

Abstract: Human adenovirus type 55 (HAdV-B55) is an acute respiratory disease (ARD) pathogen first completely characterized in China (2006). This is a unique Trojan horse microbe with the virus neutralization attribute of a renal pathogen and the cell tropism and clinical attributes of a respiratory pathogen, bypassing herd immunity. It appeared to be an uncommon pathogen, with earlier putative, sporadic occurrences in Spain (1969) and Turkey (2004); these isolates were incompletely characterized using only two epitopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 17 publications
3
48
0
1
Order By: Relevance
“…We also found emergent HAdV-14 and HAdV-21 and re-emergent HAdV-55 in Southern China, which may have potential to cause more outbreaks in this area, similar with ARD outbreaks in Northern China317182144. Remarkably, we found HAdV-14 emerged in September 2010, one month earlier than the first HAdV-14 strain reported in China21.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We also found emergent HAdV-14 and HAdV-21 and re-emergent HAdV-55 in Southern China, which may have potential to cause more outbreaks in this area, similar with ARD outbreaks in Northern China317182144. Remarkably, we found HAdV-14 emerged in September 2010, one month earlier than the first HAdV-14 strain reported in China21.…”
Section: Discussionsupporting
confidence: 75%
“…Of the seven HAdV species, species B (mostly HAdV-3, -7, -14, and -55) and species E (HAdV-4) are highly associated with ARD, which account for a high proportion of respiratory diseases both in children and adults throughout the world1211121314151617181920212223. HAdV-7 is one of the most important respiratory HAdVs and has been circulating both in military and civilian populations.…”
mentioning
confidence: 99%
“…12 It exhibited a neutralizing antigen epitope of HAdV-11 and the pathogenic properties of HAdV-14. [13][14] The whole-genome sequencing analysis showed that HAdV-55 had an HAdV-14 chassis with a partial HAdV-11 in the hexon gene. [15][16] For this reason, it was renamed HAdV-55.…”
Section: Cell Culture and Virus Isolationmentioning
confidence: 99%
“…Novel strains may arise from mutations or recombinations of two different adenovirus strains between the hexon gene and fiber genes. 3,4 Recently, an emergent variant, HAdV-55, 5,6 with a proposed recombination of hexon gene between HAdV-11 and HAdV-14 strains, has been described in association with multiple outbreaks of acute respiratory disease, mostly occurring in military camps. [7][8][9][10] In 2005, a large outbreak of acute respiratory disease likely from HAdV-55 occurred in a military camp in Turkey.…”
Section: Introductionmentioning
confidence: 99%